Gambling in Alberta: History, Current Status and Socioeconomic Impacts - Williams, Robert J.; Belanger, Yale D.; Arthur, Jennifer N. (Alberta Gaming Research Institute, 2011)
The First Section of this report elucidates our Research Approach to investigating the impacts of gambling in Alberta and our Theoretical Approach for Assessing Socioeconomic Impacts of Gambling. This theoretical approach derives from a comprehensive review of the issues involved. Because of the gradual introduction of gambling and the lack of empirical data for much of this time period, a part of the present socioeconomic analysis must necessarily be descriptive rather than empirical in nature. Thus, the Second Section of this report contains the History of Gambling in Alberta. This history indirectly speaks to the historical impacts of gambling and also provides the necessary context to understand the complex way in which gambling is provided in Alberta today. Further to this end, the second half of this section provides a comprehensive description of the Current Regulation, Availability and Provision of Legal Gambling in Alberta. The Third Section, and the main body of this report, contains the results from a more empirical analysis of the social and economic impacts of gambling. The focus of this empirical analysis is from 1970 to the present time. This is partly because of data unavailability prior to 1970; partly because 1969 was coincident with the beginning of Alberta’s ability to independently provide, regulate, and license most forms of gambling; and partly because the most rapid introduction and expansion of gambling in Alberta has occurred between the mid 1980s to the present time. Thus, this is also the period where impacts are most likely to be observed. The first part of this section is an investigation of the Amounts, Origins, and Recipients of Gambling Revenue. The second part of this section is an investigation of the Impacts of Gambling on the sectors primarily involved in the transfer and receipt of this money: the Provincial Government; Charitable Organizations; the general Alberta Populace (Society); Private Industry; and Alberta First Nations. The Fourth and final Section of this report ...